ANALISIS DAMPAK SISTEM ZONASI PADA HASIL BELAJAR GEOGRAFI DI SMA NEGERI 7 PADANG - Atika Fejerina; Afdhal Afdhal (JURUSAN GEOGRAFI FIS UNP, 2023)
The zoning system is a new policy issued by the government to accelerate the distribution of quality education. However, this zoning system seems to limit students' choices. The zoning system shows that it not only has an impact on motivation but also student learning outcomes. The purpose of this study was to determine the effect of the application of the zoning system on the level of learning outcomes of students affected by the application of the zoning system, for the object of research, namely students of class XI IPS SMA Negeri 2 Padang in the 2020/2021 academic year. This study uses a mixed approach (mix method), namely qualitative and quantitative with non-experimental research type is correlational. With a population of 412 and a sample of 60. Data collection by questionnaires, interviews, and documentation. The research instrument was tested for validity and reliability using the product moment correlation formula from Pearson and reliability testing with the Cronbach alpha formula. Data analysis used descriptive statistics of percentages and simple regression analysis. The results of the study show that the level of learning achievement of students in class XI Social Sciences SMA Negeri 2 Padang in the 2020/2021 academic year is in the weak category, and there is a significant influence on the implementation of the zoning system on the learning achievements of students in class XI SMA Negeri 7 Padang in the 2020/2021 academic year.